Giant acquired acral fibrokeratoma: A case report - Hend M. Al-Atif (PAGEPress Publications, 2019)
Acquired acral fibrokeratoma (AAF) is a rare benign fibrous tumor. Its size is usually small (i.e., <0.5 cm). However, few cases with giant lesions (i.e., >1 cm) have been reported. A 17-year-old Saudi male presented to the Dermatology Outpatient Clinic of Aseer Central Hospital, Aseer Region, Saudi Arabia, with a painless rounded skin-colored exophytic nodule arising from the dorsal surface of the right middle toe, 1.7 cm in diameter. The tumor was surgically excised. Histopathology examination revealed a giant polyploid lesion, composed of massive hyperkeratosis, acanthosis, a core of thick collagen bundles and vertically oriented small dermal blood vessels. The diagnosis was giant AAF. There was no evidence of recurrence after surgical excision. AAF is a rare benign skin tumor which should be differentiated from other similar skin lesions. Surgical excision is the first line for treatment.